2013
DOI: 10.1007/s10029-013-1146-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the contralateral inguinal ring in clinically unilateral inguinal hernia: a systematic review and meta-analysis

Abstract: Purpose The management of the contralateral inguinal canal in children with clinical unilateral inguinal hernia is controversial. Our objective was to systematically review the literature regarding management of the contralateral inguinal canal. Methods We searched MEDLINE, EMBASE, and Cochrane databases (1940–2011) using ‘hernia’ and ‘inguinal’ and either ‘pediatric,’ ‘infant,’ or ‘child,’ to identify studies of pediatric (age≤21 yrs) patients with inguinal hernia. Among clinical unilateral hernia patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 23 publications
4
43
0
2
Order By: Relevance
“…Performing contralateral hernia repair in patients with CPP results in overtreatment in roughly 2 out of 3 patients. 8,11 Our reported hernia recurrence rates are comparable to those associated with open repair. 1,9,11 However, data regarding the risk of testicular atrophy are not available as it needs long term follow up.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Performing contralateral hernia repair in patients with CPP results in overtreatment in roughly 2 out of 3 patients. 8,11 Our reported hernia recurrence rates are comparable to those associated with open repair. 1,9,11 However, data regarding the risk of testicular atrophy are not available as it needs long term follow up.…”
Section: Discussionsupporting
confidence: 64%
“…Although contralateral repair in patients with CPP may reduce the incidence of MCH, such a strategy will result in significant overtreatment since a majority of these patients will not develop clinical MCH. 6,8 The literature suggests that laparoscopically identified CPP is a poor indicator of future contralateral hernia. Almost a third of patients will have a CPP, while less than one in 10 will develop MCH when managed expectantly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports stated that laparoscopic contralateral internal inguinal ring observation was attempted from the early 1990s [25]. A contralateral PPV was seen in 6-66 % of cases [16,[25][26][27][28][29][30][31][32]; the range is very wide. This seems to be because the way of observing the contralateral internal ring varied in each study.…”
Section: Discussionmentioning
confidence: 95%
“…25,29 Yet, a meta-analysis revealed that only 6% of all patients returned with MCH after unilateral inguinal hernia repair. 26 Thus, the presence of CPPV does not necessarily equate to subsequent clinical inguinal hernia.…”
Section: Contralateral Explorationmentioning
confidence: 99%
“…26 Thus, the presence of CPPV does not necessarily equate to subsequent clinical inguinal hernia. Kokorowski et al 29 concluded that patent processus vaginalis might be over-treated. Repair of the patent processus vaginalis will definitely decrease the risk of MCH, the costs, and the risk of future hernia incarceration.…”
Section: Contralateral Explorationmentioning
confidence: 99%